Receptor Activity and Conformational Analysis of 5’-Halogenated Resiniferatoxin Analogues as TRPV1 Ligands - Lim, Kwang Su (2010)
A series of 5’-halogenated resiniferatoxin analogues have been investigated in order to examine the effect of halogenation in the A-region on their binding and the functional pattern of agonism/antagonism for rat TRPV1 heterologously expressed in Chinese hamster ovary cells. Halogenation at the 5-position in the A-region of RTX and of 4-amino RTX shifted the agonism of parent compounds toward antagonism. The extent of antagonism was greater as the size of the halogen increased (I > Br > Cl > F) while the binding affinities were similar, as previously observed for our potent agonists. In this series, 5-bromo-4-amino RTX (39) showed very potent antagonism with K(i(ant)) = 2.81 nM, which was thus 4.5-fold more potent than 5’-iodo RTX, previously reported as a potent TRPV1 antagonist. Molecular modeling analyses with selected agonists and the corresponding halogenated antagonists revealed a striking conformational difference. The 3-methoxy of the A-region in the agonists remained free to interact with the receptor whereas in the case of the antagonists, the compounds assumed a bent conformation, permitting the 3-methoxy to instead form an internal hydrogen bond with the C4-hydroxyl of the diterpene.